2020
DOI: 10.4103/jgid.jgid_397_20
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 blind spots: A consensus statement on the importance of competent political leadership and the need for public health cognizance

Abstract: As the COVID-19 pandemic continues, important discoveries and considerations emerge regarding the SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2) pathogen; its biological and epidemiological characteristics; and the corresponding psychological, societal, and public health (PH) impacts. During the past year, the global community underwent a massive transformation, including the implementation of numerous nonpharmacological interventions; critical diversions or modifications across various spheres o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 185 publications
0
13
0
2
Order By: Relevance
“…This follows suit with the messaging coming from both medical and political leaders did not always correspond and thus led to confusion among the public, particularly when it came to mask-wearing. This lack of knowledge of public health principles and the overall politicization of COVID-19 regarding knowledge, quarantine, and tracing efforts have demonstrated that "it is important to ensure that properly trained personnel are empowered to act in a purely nonpolitical manner" [14].…”
Section: Discussionmentioning
confidence: 99%
“…This follows suit with the messaging coming from both medical and political leaders did not always correspond and thus led to confusion among the public, particularly when it came to mask-wearing. This lack of knowledge of public health principles and the overall politicization of COVID-19 regarding knowledge, quarantine, and tracing efforts have demonstrated that "it is important to ensure that properly trained personnel are empowered to act in a purely nonpolitical manner" [14].…”
Section: Discussionmentioning
confidence: 99%
“…Papadimos et al 43 Global Deploying point-of-care diagnostics and focusing on telemedicine platforms (albeit challenges like suboptimal internet connectivity or insufficient encryption) have the potential to enhance screening efforts and prevent excess TB mortality.…”
Section: Existing Challenges In Tb Prevention and Controlmentioning
confidence: 99%
“…48,52,53 Political commitment is essential to support core health care services that sustain high-quality point-ofcare diagnostics and treatment plans for TB patients as well as balancing these needs with the coexisting pandemic. 19,37,[41][42][43] These actions can focus on long-term and comprehensive care for TB and coexisting priorities like COVID-19. 6,32,36,45 Following the World Health Organization's call that all nations should conduct and utilize research capacity, researchers can investigate key scientific questions raised during coinciding pandemics.…”
Section: Ensuring Leadership and Governance For Sustainable National Health Budgetsmentioning
confidence: 99%
See 2 more Smart Citations